"Family Values" in the Gospel Tradition. Issue 3 (October 2019) - Frey, Jörg
This article discusses the idea of "family values, " developed in modern Western Protestantism, within the horizon of family-related sayings in the Gospel tradition. In accord with general tendencies of the Hellenistic period, early Christianity opened up the possibility of a religious affiliation different from that suggested by ethnic, tribal, or familial tradition. A first challenge to traditional family obligations can be seen in the lifestyle of Jesus and his earliest disciples: In Mark, Jesus is depicted in a strong distance from his physical family. Common family obligations are questioned, and those who follow him and God's word are called his real family. In Matthew and Luke, the distance is softened due to the idea that Jesus' family is already aware of his mission and destiny. In John, his earthly mother is present under his cross, and also Joseph as his father is openly mentioned, but his true origins are in the realm of God, and for his Galilean contemporaries, knowledge of his earthly origins is rather an argument not to believe him. In John, finally, family aspects are transferred to the community which is the new family of God, shaped by the mutual love and support of the disciples. In a global context of theology, the various biblical views on family matters and also the different patterns of community structures have to be negotiated, and the challenge of the radical questioning of traditional values in Jesus' ministry should not be ignored.